Factors affecting ovipositional behaviour of Scutellista cyanea, an egg-parasitoid of hemispherical scale [Saissetia] - Abdul Ghani Ibrahim (Universiti Pertanian Malaysia, Serdang, Selangor. Dept. of Plant Protection) (2013)
Scutellista cyanea Motschulsky is an egg parasitoid of many coccids, including the hemispherical scale, Saissetia coffeae. The adult female parasitoid oviposits in gravid scale, S. coffeae. Ambient temperature influences the number of eggs deposited and adult longevity of the parasitoid. The life-span of the adult parasitoid was found to be reduced with an increase in temperature; at 20 deg C. longevity it was 80.0 days while at 28 deg C. it was only 30 days. On the other hand, an increase in temperature within limits would increase the total number of eggs deposited by the parasitoid. In a comparison of two sizes of host-scale i.e., scale 3.5 mm in length and 2.5 mm in length, the result showed that significantly (p0.05) greater parasitoid progency emerged from host scale of 3.5 mm in length. The relationship between head width and adult longevity and between head width and egg production are r